Modelling integrated antiretroviral treatment and harm reduction services on HIV and overdose among people who inject drugs in Tijuana, Mexico. (19th June 2020) - Cepeda, Javier A; Bórquez, Annick; Magana, Christopher; Vo, Anh; Rafful, Claudia; Rangel, Gudelia; Medina‐Mora, María E; Strathdee, Steffanie; Martin, Natasha K
Abstract: Introduction: The HIV epidemic in Tijuana, Mexico is concentrated in key populations, including people who inject drugs (PWID). However, HIV interventions among PWID are minimal, and federal funding was provided for compulsory abstinence programmes associated with HIV and overdose. Alternatively, opioid agonist therapy reduces overdose, reincarceration, HIV, while improving antiretroviral therapy (ART) outcomes. We assessed potential impact and synergies of scaled‐up integrated ART and opioid agonist therapy, compared to scale‐up of each separately, and potential harms of compulsory abstinence programmes on HIV and fatal overdose among PWID in Tijuana. Methods: We developed a dynamic model of HIV transmission and overdose among PWID in Tijuana. We simulated scale‐up of opioid agonist therapy from zero to 40% coverage among PWID. We evaluated synergistic benefits of an integrated harm reduction and ART scale‐up strategy (40% opioid agonist therapy coverage and 10‐fold ART recruitment), compared to scale‐up of each intervention alone or no scale‐up of low coverage ART and no harm reduction). We additionally simulated compulsory abstinence programmes (associated with 14% higher risk of receptive syringe sharing and 76% higher odds of overdose) among PWID. Results: Without intervention, HIV incidence among PWID could increase from 0.72 per 100 person‐years (PY) in 2020 to 0.92 per 100 PY in 2030. Over ten years, opioid agonist therapy scale‐up could avert 31% (95% uncertainty interval (UI): 18%, 46%) and 22% (95% UI: 10%, 28%) new HIV infections and fatal overdoses, respectively, with the majority of HIV impact from the direct effect on HIV transmission due to low ART coverage. Integrating opioid agonist therapy and ART scale‐up provided synergistic benefits, with opioid agonist therapy effects on ART recruitment/retention averting 9% more new infections compared to ART scale‐up alone. The intervention strategy could avert 48% (95% UI: 26%, 68%) of new HIV infections and one‐fifth of fatal overdoses over ten years. Conversely, compulsory abstinence programmes could increase HIV and overdoses. Conclusions: Integrating ART with opioid agonist therapy could provide synergistic benefits and prevent HIV and overdoses among PWID in Tijuana, whereas compulsory abstinence programmes could cause harm. Policymakers should consider the benefits of integrating harm reduction and HIV services for PWID.